Impact of event notification services on timely follow-up and rehospitalization among primary care patients at two Veterans Affairs Medical Centers. (1st October 2021) - Dixon, Brian E; Judon, Kimberly M; Schwartzkopf, Ashley L; Guerrero, Vivian M; Koufacos, Nicholas S; May, Justine; Schubert, Cathy C; Boockvar, Kenneth S
Abstract: Objective: To examine the effectiveness of event notification service (ENS) alerts on health care delivery processes and outcomes for older adults. Materials and methods: We deployed ENS alerts in 2 Veterans Affairs (VA) medical centers using regional health information exchange (HIE) networks from March 2016 to December 2019. Alerts targeted VA-based primary care teams when older patients (aged 65+ years) were hospitalized or attended emergency departments (ED) outside the VA system. We employed a concurrent cohort study to compare postdischarge outcomes between patients whose providers received ENS alerts and those that did not (usual care). Outcome measures included: timely follow-up postdischarge (actual phone call within 7 days or an in-person primary care visit within 30 days) and all-cause inpatient or ED readmission within 30 days. Generalized linear mixed models, accounting for clustering by primary care team, were used to compare outcomes between groups. Results: Compared to usual care, veterans whose primary care team received notification of non-VA acute care encounters were 4 times more likely to have phone contact within 7 days (AOR = 4.10, P  < .001) and 2 times more likely to have an in-person visit within 30 days (AOR = 1.98, P  = .007). There were no significant differences between groups in hospital or ED utilization within 30 days of index discharge ( P  = .057). Discussion: ENS was associated with increased timely follow-up following non-VA acute care events, but there was no associated change in 30-day readmission rates. Optimization of ENS processes may be required to scale use and impact across health systems. Conclusion: Given the importance of ENS to the VA and other health systems, this study provides guidance for future research on ENS for improving care coordination and population outcomes. Trial Registration: ClinicalTrials.gov NCT02689076. "Regional Data Exchange to Improve Care for Veterans After Non-VA Hospitalization." Registered February 23, 2016.